Pengaruh Leverage, Pembiayaan Mudharabah, Musyarakah, Murabahah, dan Ijarah Terhadap Kinerja Keuangan Bank Umum Syariah di Indonesia - Tri Puspita Ningtyas; Mochamad Fariz Irianto; Ati Retna Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to examine how Leverage, Mudharabah, Musyarakah, Murabahah, and Ijarah financing affect financial performance registered with the Financial Services Authority for the period 2021-2023. This study uses purposive sampling and multiple linear regression analysis processed with SmartPlS. The results of the study indicate that only Mudhrabah and Ijarah financing affect financial performance. Meanwhile Leverage, musyarakah and murabahah financing do not affect financial performance. This study contributes theoretically to add to the literature on financial performance and provides practical benefits for management in making the right financial decisions.